2013
DOI: 10.1515/ntrev-2012-0078
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of graphene and graphene oxide with proteins and peptides

Abstract: This review selectively describes the recent progress in the interactions of proteins (enzymes) and shortchain peptides with graphene and graphene oxide (GO). Particularly, the advances of the immobilization mechanisms of enzymes on graphene and GO, the catalytic properties of the immobilized enzymes, and their applications are summarized in detail. The interfacings of the peptides with graphene and GO, the as assembled conjugates, and their potential applications are discussed briefly. The possible ongoing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(119 citation statements)
references
References 49 publications
4
115
0
Order By: Relevance
“…The interconnected two-dimensional (2D) substrates could be served as a platform for enzyme immobilization through non-covalent adsorption and covalent binding [26]. Zeta potential measurements showed that after the surface modification with Fe 3 O 4 nanoparticles, the Zeta potential value of GO dramatically changed from −43.7 mV to +31.5 mV.…”
Section: Characterization Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…The interconnected two-dimensional (2D) substrates could be served as a platform for enzyme immobilization through non-covalent adsorption and covalent binding [26]. Zeta potential measurements showed that after the surface modification with Fe 3 O 4 nanoparticles, the Zeta potential value of GO dramatically changed from −43.7 mV to +31.5 mV.…”
Section: Characterization Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…Several studies have reported the immobilization of peptides and enzymes on GO via covalent bonding or non-covalent interactions (Pavlidis et al, 2012;Su et al, 2012;Zhang et al, 2010;Zhang et al, 2011;Zhang et al, 2013). Alkaline protease immobilized on GO exhibited enhanced thermal stability at its optimum temperature of 60°C (Su et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When the pH value of the initial GO suspension increases via the ammonia addition, the Fe 2+ ions co−precipitate with the acquired Fe 3+ ions into Fe3O4, leading to the formation of rGO−Fe3O4 nanocomposites. Subsequently, the CAT is directly adsorbed on the surface of as-prepared rGO−Fe3O4 nanocomposites via the multiple interactions (hydrogen bonding and hydrophobic interaction) between CAT and rGO−Fe3O4 surface to acquire the rGO−Fe3O4−CAT[17,36]. As for the biomimetic adhesion, a polydopamine (pDA) layer was firstly functionalized and wrapped on the surface of rGO−Fe3O4 nanocomposites (the preparation process of rGO−Fe3O4−pDA is presented in the Supplementary data).…”
mentioning
confidence: 99%